Low back pain induces disability of women in primary uncomplicated pregnancy - Korovessis, Panagiotis; Antonaki, Rania; Zacharatos, Spyridon; Syrimpeis, Vasileios (Clinical Journal of Obstetrics and Gynecology, 2019)
Study design: A consecutive case series study Purpose: To investigate whether Low Back Pain (LBP) in women with primary singleton pregnancy induces disability. Background: LBP is reported to be increased in pregnants than in non-pregnant women. Different outcome measures have been used to search for correlations between pain and disability. Methods: 167 pregnant women aged 30 ± 3.5 years participated. Two equal categorial age groups were constructed: Group A included women aged 23 - 29 years, and Group B women aged 30-39 years. Their weight was 76 ± 13 kg prepartum and the Body Mass index (BMI) was 28 ± 4 prepartum. Visual Analogue Scale (VAS) was used for LBP pain intensity and Oswestry Disability Scale (ODI) for disability estimation in the last three months prepartum and in the first three months postpartum. Results: The women weight was 67 ± 13 kg postpartum. The BMI was 24 ± 4 postpartum. There was no difference in VAS and ODI scores versus BMI, weight and height between the two age groups in both periods of observation: prepartum and postpartum. Prepartum, 81.4% of women claimed LBP that dropped to 55.5% postpartum. ODI score dropped from 19.5 ± 13.6% prepartum to 11 ± 12% postpartum. The ODI subscales that showed significant reduction postpartum were: Pain intensity (P = 0.002); working (P = 0.009); sitting (P = 0.004); standing (P = 0.003); sleeping (P = 0.008); and traveling (P = 0.006). VAS prepartum was increasing as the weight was increasing in both periods of observation (P = 0.015 and P=0.051) respectively. VAS prepartum was significantly correlated with BMI prepartum (P = 0.019) and postpartum (P = 0.028). Discussion: Physical disability in pregnant women was low and reduced following delivery. Disability was linked with LBP intensity, weight, BMI and height, but not with age or educational level.